Manajemen risiko pada produk hybrid syariah di tengah inovasi keuangan modern - Setyawan, Ahmad Bayu (Maliki Interdisciplinary Journal, 2026)
The development of digitally-based financial technology, particularly fintech, has led to significant changes in the Islamic banking sector, including through the creation of hybrid products (multi-contract). These products provide flexibility and efficiency in meeting complex transaction needs, although they also increase the complexity of contract structures, resulting in higher risks. The aim of this study is to identify the risk characteristics associated with Islamic hybrid products and to develop relevant risk management strategies to address the challenges of modern financial innovation. The approach used in this study is qualitative with a literature study method from various relevant academic sources in the fields of Islamic banking, risk management, and financial technology. The analysis conducted shows that the main risks faced include sharia compliance risk, operational risk, and technological risks, which become increasingly complex with the integration of digital systems. In addition, the implementation of technology also brings about additional risks such as cyber threats, information leaks, and system failures. Therefore, the implementation of an integrated risk management framework based on Enterprise Risk Management (ERM) is required, supported by the use of digital technology, strengthening of internal control systems, and optimization of the role of the Sharia Supervisory Board. The implications of this study emphasize that the collaboration between technological innovation and Sharia principles is very important in maintaining the stability, trust, and sustainability of the Sharia banking sector.